Pembentukan Perda yang Demokratis - Astomo, Putra (UIN Sunan Kalijaga Yogyakarta, 2012)
Regulation is one of the products of legislation local level. Regulation contains rules that govern all matters relating to the region in order to realize a fair society and aprosperous society. The legal, political, economic, social, and cultural factors thatinfluence a formation law. Regulation in shades of democracy and regional autonomyshould reflect the interests of the public, especially in the areas concerned in orderlegislation does not reflect the interests of local elites alone. This paper aims to find outabout how the establishment of democratic regulation.